Mapping Islamic banking and sustainable development research: A Scopus-based bibliometric and VOSviewer keyword co-occurrence cluster analysis (2008–2024) - Garbo, Anom; Hasanah, Shofia Mauizotun (Universitas Islam Indonesia, 2025)
IntroductionSustainable development has become a central paradigm in contemporary finance, shaping how banking institutions align capital allocation, governance, and social value creation with long-term development goals. Within this context, Islamic banking is increasingly examined as a values-driven system that may support sustainable development through ethical foundations, Sharia compliance, and inclusion-oriented financial practices. However, the expanding literature remains fragmented across themes, methods, and policy debates, creating a need for systematic mapping of its intellectual structure and research frontiers.ObjectivesThis study aims to (1) map the evolution and distribution of research on Islamic banking and sustainable development, (2) identify dominant and emerging thematic clusters through keyword co-occurrence, and (3) highlight research gaps and future directions that can inform theory development, banking practice, and sustainability-oriented policy.MethodThis study employs a bibliometric approach using Scopus metadata retrieved through the query (TITLE-ABS-KEY ( islamic AND bank ) AND TITLE-ABS-KEY (